Five things to know about the Australian Constitution / Helen Irving. - Irving, Helen (Cambridge University Press, 2004)
In this excellent new book, Helen Irving delves into the mystery that is the Australian constitution by discussing the major national debates of recent years. Many people want to understand and take part in the debate about constitutional issues but they face a significant hurdle: the constitution is almost unreadable. It does not mean what it says, and nor does it say what it means. There are many myths in circulation about what the constitution says and as many assumptions about what it does. Helen Irving, one of this country's foremost constitutional experts, puts various constitutional confusions to rest, and invites a general audience into an understanding of the issues that were once reserved for experts.